Perovskite thin film, cell and preparation method
By using porous lead halide skeleton layer and dehydrated pore-forming agent in the perovskite film preparation process, the problems of insufficient reaction and short age of lead halide layer in the two-step preparation of perovskite film were solved, and efficient and uniform perovskite film preparation and improved solar cell performance were achieved.
Patent Information
- Application Number
- CN202411758253.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the two-step method is used to prepare perovskite films, which have problems such as insufficient reaction between the lead halide layer and the organic amine salt and short storage age of lead halide layer, resulting in low conversion efficiency, poor film formation quality and low production efficiency.
The porous lead halide framework layer is prepared by evaporation on the initial film layer, and the dehydration and volatile properties of the pore-forming agent are used to promote the full penetration and reaction of the organic amine salt solution to form a high-quality perovskite film.
The film formation quality and conversion efficiency of perovskite film are improved, the age of lead halide layer is extended, and the moisture-heat stability and photoelectric conversion performance of perovskite film are enhanced.
Smart Images

Figure CN119654039A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solar cells, and more specifically, to a method for preparing a perovskite film, a perovskite cell and a method for preparing the same, and a stacked cell and a method for preparing the same. Background Art
[0002] At present, the application research field of perovskite materials in solar cells has made certain positive progress. The mainstream perovskite film preparation methods can be divided into one-step method and two-step method. Among them, the one-step method is to mix lead halide salt and organic amine salt in a solvent, and directly obtain the perovskite film through one-step deposition; the two-step method is to first deposit the lead halide film, and then react the organic amine salt with the lead halide film to form a perovskite film. Compared with the one-step method, the two-step method for preparing perovskite films has the technical advantages of being more environmentally friendly and highly stable.
[0003] However, the two-step method used in the related art to prepare perovskite films still has problems such as insufficient reaction of the lead halide layer with the organic amine salt solution and short storage time of the lead halide layer, which further leads to low conversion efficiency, poor film quality of the perovskite film and low production efficiency, seriously affecting the electrical performance of solar cells.
[0004] Based on this, how to optimize the preparation process of perovskite thin films, improve the film formation quality of perovskite thin films, and then ensure and improve the performance of solar cells is an urgent problem to be solved in this field. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present application provides a method for preparing a perovskite film, a method for preparing a perovskite cell, a stacked cell and a method for preparing the same.
[0006] As a first aspect of the present invention, a method for preparing a perovskite thin film is provided, the preparation method comprising:
[0007] Providing an initial film layer, the initial film layer comprising a first surface and a second surface opposite to each other;
[0008] Providing a coating material, the coating material comprising: lead halide and a pore-forming agent; wherein the pore-forming agent has a dehydrating property;
[0009] The coating material forms a porous lead halide skeleton layer with a preset porosity on the first surface of the initial film layer through an evaporation process;
[0010] Coating a mixed solution of organic amine salts on a side of the porous lead halide skeleton layer away from the initial film layer to react and form an initial perovskite film;
[0011] The initial perovskite film is subjected to a first type annealing treatment to form the perovskite film.
[0012] Furthermore, the molecular formula of the pore former has a —N═C═N— functional group.
[0013] Furthermore, the pore-forming agent includes at least one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide.
[0014] Furthermore, the step of forming a porous lead halide skeleton layer with a preset porosity on the first surface of the initial film layer by the coating material through an evaporation process comprises:
[0015] Heating the container containing the lead halide and the container containing the pore-forming agent respectively, so that the lead halide and the pore-forming agent evaporate and are co-deposited on the first surface of the initial film layer to form a lead halide layer;
[0016] The lead halide layer is subjected to a second type annealing treatment so that the pore former is evaporated by heat to form the porous lead halide skeleton layer; wherein the ratio of the deposition rate of the lead halide to the deposition rate of the pore former is between 10:1 and 20:1; and the preset porosity is between 1% and 30%.
[0017] Furthermore, the heating temperature of the lead halide is in the range of 350°C to 480°C; the deposition rate of the lead halide is in the range of to The heating temperature of the pore-forming agent is in the range of 80°C to 130°C; the deposition rate of the pore-forming agent is to between.
[0018] Furthermore, in the step of performing a second type annealing treatment on the lead halide layer, the annealing temperature is not lower than the boiling point of the pore former; wherein the annealing temperature is in the range of 150° C. to 170° C.; and the annealing time is between 3 min and 7 min.
[0019] Further, a mixed solution of organic amine salts is coated on a side of the porous lead halide skeleton layer away from the initial film layer to react to form an initial perovskite film, and the initial perovskite film is subjected to a first type annealing treatment to form the perovskite film.
[0020] The solute in the organic ammonium salt solution is selected from at least one of formamidine hydroiodide, formamidine hydrobromide, methylammonium iodide, methylammonium bromide and methylammonium chloride;
[0021] The solvent in the organic ammonium salt solution is selected from at least one of isopropanol, ethanol and methanol;
[0022] In the first type annealing treatment, the annealing temperature is in the range of 120° C. to 160° C.; and the annealing time is in the range of 5 min to 30 min.
[0023] As a second aspect of the present invention, a method for preparing a perovskite battery is provided, comprising:
[0024] providing a first transparent conductive layer;
[0025] forming a first carrier transport layer on one side of the first transparent conductive layer;
[0026] Using the first carrier transport layer as an initial film layer, and using the above-mentioned preparation method to prepare a perovskite film on a side of the first carrier transport layer away from the first transparent conductive layer;
[0027] A second carrier transport layer, a second transparent conductive layer and a metal electrode stacked in sequence are formed on a side of the perovskite film away from the first carrier transport layer.
[0028] As a third aspect of the present invention, a method for preparing a stacked battery is provided, comprising:
[0029] A crystalline silicon bottom cell is provided; the crystalline silicon bottom cell comprises a front side and a back side opposite to each other;
[0030] A perovskite cell is prepared on the front side of the crystalline silicon bottom cell; wherein,
[0031] The perovskite battery is prepared by the above-mentioned method for preparing the perovskite battery;
[0032] The crystalline silicon bottom cell includes: a PERC cell, a BC cell, a HJT cell or a TOPCon cell.
[0033] As a fourth aspect of the present invention, a stacked cell is provided, which is prepared by the stacked cell preparation method as described above; the stacked cell comprises: a crystalline silicon bottom cell and a perovskite cell stacked in sequence, wherein the crystalline silicon bottom cell comprises: a PERC cell, a BC cell, a HJT cell or a TOPCon cell.
[0034] In the preparation method of the perovskite film provided in the present application, a two-step method is adopted to prepare the perovskite film on the initial film layer. First, a porous lead halide skeleton layer with a preset porosity is prepared by a dry evaporation process, and then an organic amine salt is coated and fully penetrated into the porous lead halide skeleton layer by a wet coating process, and then a perovskite film is formed by annealing. The preparation method is safe and environmentally friendly, and the film quality of the formed perovskite film is more uniform.
[0035] In the process of preparing a porous lead halide skeleton layer by evaporation process, the evaporation gas introduces lead halide gas and pore-forming agent, so that the lead halide film layer formed by evaporation is uniformly doped with the pore-forming agent. The advantage of this preparation method is that the pore-forming agent has the characteristic of being volatile and can destroy the dense lead halide film layer prepared by evaporation. The pore-forming agent evaporates from the lead halide film layer to produce gas, leaving evenly distributed holes in the lead halide film layer, so that the density of the lead halide film layer is reduced, loose and porous, and a film layer with a porous lead halide skeleton structure is created, which is effective for the second step of the wet method. Organic amine salt solution coating is more advantageous. Organic amine salt solution can fully penetrate into the porous lead halide skeleton in the form of liquid, so that the two can fully contact and mix and chemically react to form a perovskite film, which enhances the conversion and crystallization of the perovskite film, thereby avoiding the lead halide film layer being too dense, resulting in insufficient penetration of organic amine salts and insufficient reaction, resulting in residues in the lead halide film layer, leading to a decrease in the electrical properties of the perovskite film; in addition, the pore former is volatile and evaporates in the subsequent heating process, avoiding the introduction of impurities that affect the synthesis quality of the perovskite film.
[0036] On the other hand, this pore-forming agent has dehydrating properties and can capture hydrogen and oxygen atoms in the lead halide film layer and react chemically, so that the lead halide film layer reduces the adsorption of water molecules. The pore-forming agent effectively slows down the moisture absorption of the lead halide film layer, so that when the lead halide film layer reacts with the subsequent organic amine salt to form perovskite, the reaction between the formed perovskite and the water in the lead halide layer is significantly reduced, thereby avoiding further hydrolysis of the perovskite, and ultimately preventing the performance degradation caused by the hydrolysis of the perovskite. The introduction of this pore-forming agent also solves the key problem of the short aging time of the lead halide film layer after preparation in the traditional two-step process, and increases the process window time after the lead halide film layer is prepared. When the two-step method is used to prepare the perovskite film, the lead halide film layer does not have to react with the organic amine salt and convert into perovskite immediately after preparation. This provides a feasible solution for the subsequent large-scale industrial preparation of perovskite. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic flow chart of a method for preparing a perovskite film provided in some embodiments of the present application;
[0038] Figure 2 A schematic flow chart of a method for preparing a perovskite battery provided in some embodiments of the present application;
[0039] Figure 3 A schematic diagram of the structure of a perovskite battery provided in some embodiments of the present application;
[0040] Figure 4 A schematic diagram of a process for preparing a stacked battery provided in some embodiments of the present application;
[0041] Figure 5 A schematic diagram of the structure of a stacked battery provided in some embodiments of the present application;
[0042] FIG6( a) is a scanning electron microscope photograph of the lead halide layer prepared in Example 1 of the present application;
[0043] FIG6( b) is a scanning electron microscope photograph of the lead halide layer prepared in Comparative Example 1 of the present application;
[0044] FIG7( a) is a macroscopic optical photograph of the perovskite film prepared in Example 1 of the present application;
[0045] FIG7( b ) is a macroscopic optical photograph of the perovskite film prepared in Comparative Example 1 of the present application;
[0046] Figure 8 X-ray diffraction test diagram of the perovskite film prepared in Example 1 and Comparative Example 1 of the present application;
[0047] Fig. 9 The current-voltage curves of the perovskite cells prepared in Example 2 and Comparative Example 2 of the present application;
[0048] Fig.10 The current-voltage curves of the perovskite cells prepared in Example 3 and Comparative Example 3 of the present application;
[0049] Fig.11 The current-voltage curves of the crystalline silicon-perovskite tandem cells prepared in Example 4 and Comparative Example 4 of the present application.
[0050] Description of reference numerals:
[0051] 1-Perovskite battery; 2-Crystalline silicon bottom battery;
[0052] 11a-first transparent conductive layer; 11b-second transparent conductive layer; 11c-third transparent conductive layer; 12-first carrier transport layer; 13-perovskite film; 14-second carrier transport layer; 15a-first metal electrode; 15b-second metal electrode; 21-first type doped silicon layer; 22-intrinsic layer; 23-silicon substrate; 24-second type doped silicon layer. DETAILED DESCRIPTION
[0053] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments based on the embodiments are intended to be used to explain the present application and cannot be understood as limiting the present application.
[0054] References to "one embodiment" or "an example" or "an example" in this specification mean that a particular feature, structure, or characteristic described in conjunction with the embodiment itself may be included in at least one embodiment disclosed in the present application. The appearance of the phrase "in one embodiment" in various places in the specification does not necessarily refer to the same embodiment.
[0055] The conventional two-step method adopts a dry-wetting preparation method to prepare perovskite. Specifically, a lead halide film is firstly dry-evaporated, and then an organic amine salt solution is wet-spin-coated on the evaporated lead halide film and then annealed to prepare a perovskite film. However, the inventors have found that this technical means still faces some problems, among which the most prominent is the conversion problem of the lead halide film deposited in the first process. The lead halide film itself does not have conductivity. In order to achieve good photoelectric performance, it is necessary to ensure that the organic amine salt solution used in the second step reacts completely with the lead halide film deposited in the first step to generate a cubic phase perovskite. However, the lead halide film prepared by the dry evaporation process has a high density, which will hinder the continuous penetration of the organic amine salt solution in the second step into the lead halide film, so that the organic amine salt solution can only react with the lead halide on the surface to generate perovskite, which results in the lead halide at the bottom being unable to contact with the organic amine salt solution and undergo effective chemical conversion, resulting in residual lead halide at the bottom, low conversion rate of perovskite, and poor conductivity of the prepared perovskite layer, which seriously affects the performance of solar cells.
[0056] On the other hand, the inventors have found that another major factor affecting the performance of solar cells is the hydrolysis of perovskite, and a key factor leading to the hydrolysis of perovskite is that in the two-step process of preparing perovskite film, the lead halide film prepared in the first step adsorbs water molecules. These water molecules are adsorbed on the lead halide film in various ways, and can be adsorbed by van der Waals forces, by electrostatic adsorption, by chemical bonds, or by some defective positions on the surface and inside of the film. The longer the lead halide film is placed after preparation, the more obvious its hygroscopic effect is, the more water is adsorbed and the less it disappears. These water molecules can interact with the perovskite crystals in the subsequent process of forming the perovskite film, accelerating the hydrolysis of the perovskite, resulting in a decrease in the performance of the solar cell. Effectively controlling and reducing the water adsorbed by the lead halide film can prevent the hydrolysis of the perovskite and slow down the attenuation of the battery performance.
[0057] In order to prevent perovskite from being degraded by water, the conventional practice in the industry is to place the two-step perovskite film preparation in a vacuum drying oven. At the same time, after preparing the lead halide film in the first step, the standing time is reduced and the second step of wet organic amine salt solution spin coating is immediately performed. The purpose is to control and reduce the adsorbed moisture by reducing the standing time as much as possible. However, this method significantly increases the difficulty of preparation, and the control process is unstable, and water molecules will still be adsorbed, resulting in subsequent degradation of the perovskite. At the same time, this is also not conducive to large-scale industrial production.
[0058] The inventors of the present application further discovered that the quality of the lead halide film prepared in the first step is the key to forming a high-performance perovskite film. By introducing a pore-forming agent into the lead halide film in the first step, the pore-forming agent can evaporate into a gas and leave holes in the lead halide film to create a lead halide film with a porous skeleton structure. Although the lead halide film with a porous structure has a larger specific surface area and can improve the subsequent reaction activity of the lead halide film, it makes the lead halide film more likely to absorb moisture in the environment. However, the pore-forming agent introduced in the present application also has additional dehydration properties, which can plunder water molecules adsorbed on the lead halide film and react chemically with them, further forming a porous skeleton and dehydrated lead halide film, so that the subsequent organic amine salt solution reacts with the lead halide film of this structure and fully penetrates to form a perovskite film with high crystallinity, high conversion rate, few defects and high performance. Due to the dehydration effect, the formed perovskite film is not easy to be hydrolyzed in water, and the wet heat stability and photoelectric conversion efficiency of the corresponding battery are also improved at the same time.
[0059] In view of this, the present application provides a method for preparing a perovskite film, such as Figure 1 As shown, the method for preparing the perovskite film at least includes steps S100 to S140, specifically:
[0060] In step S100, an initial film layer is provided, wherein the initial film layer includes a first surface and a second surface opposite to each other;
[0061] In step S110, a coating material is provided, the coating material comprising: lead halide and a pore-forming agent; wherein the pore-forming agent has a dehydrating property;
[0062] In step S120, the coating material forms a porous lead halide skeleton layer with a preset porosity on the first surface of the initial film layer through an evaporation process;
[0063] In step S130, a mixed solution of organic amine salts is coated on a side of the porous lead halide skeleton layer away from the initial film layer to react and form an initial perovskite film;
[0064] In step S140 , a first type annealing treatment is performed on the initial perovskite film to form a perovskite film.
[0065] In step S100, there is no particular limitation on how to obtain the initial film layer, which may be obtained by purchasing from outside or by preparation. In some embodiments, providing the initial film layer includes:
[0066] S101. Provide a first transparent conductive layer. Preferably, the first transparent conductive layer is selected from indium tin oxide. Indium tin oxide is plated on a substrate by magnetron sputtering to obtain the first transparent conductive layer. In some embodiments, conductive glass of indium tin oxide or an indium tin oxide layer can also be directly selected as the first transparent conductive layer.
[0067] S102, forming a first carrier transport layer (e.g., a hole transport layer) on one side surface of the first transparent conductive layer to obtain an initial film layer. The present invention does not specifically limit how to form the hole transport layer, which may be an inorganic metal oxide, such as any one of nickel oxide, aluminum oxide, molybdenum oxide, or vanadium oxide, or an organic polymer, such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] and other conventional hole transport layer materials. Preferably, the hole transport layer uses nickel oxide with a thickness of 20 nm.
[0068] In step S110, the present invention does not specifically limit the lead halide component in the coating material, and the lead halide component of the conventional two-step method can be used, for example, PbX2 (wherein X=I, Br, Cl), that is, it can be at least one of lead iodide, lead bromide and lead chloride.
[0069] The present invention does not impose any special restrictions on the pore-forming agent, and only needs to satisfy that the pore-forming agent can volatilize from the lead halide layer and has dehydration properties. The reason for the pore-forming effect of the pore-forming agent here is that it is easy to volatilize, and volatilizes into gas and is discharged from the surface of the lead halide layer to form holes in the lead halide layer. In some prior arts, in order to form holes in the lead halide layer, many pore-forming agents are introduced, which can be volatile organic salts or inorganic salts, such as carbonates such as ammonium acetate, ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, sodium bicarbonate, and acetates such as ammonium acetate, all of which have volatile characteristics. However, although these pore-forming agents can volatilize and form holes in the lead halide layer after heating, this will significantly increase the specific surface area of the lead halide layer, and its adsorption performance will also significantly increase, making it easier to absorb more water, causing the subsequent formation of perovskite film to hydrolyze, resulting in significant performance degradation.
[0070] Based on this point, the pore-forming agent of the present invention has a dehydrating property in addition to the pore-forming function, and can capture the hydrogen and oxygen atoms in the lead halide layer and react chemically, so that the lead halide layer reduces the adsorption of water molecules, and in the subsequent volatilization process, the water molecules are taken away together to form a dehydrated porous lead halide skeleton layer.
[0071] In addition, the pore-forming agent effectively slows down the moisture absorption of the lead halide layer, so that when the lead halide layer reacts with the subsequent organic amine salt solution to form perovskite, the reaction of the formed perovskite with the water in the lead halide layer is significantly reduced, thereby avoiding further hydrolysis of the perovskite, and ultimately preventing the performance degradation caused by the hydrolysis of the perovskite. The introduction of this pore-forming agent also solves the key problem of the short aging time of the lead halide film layer after preparation in the traditional two-step process, and increases the process window time after the preparation of the lead halide layer. When the two-step method is used to prepare the perovskite film, the lead halide layer does not need to react with the organic amine salt and convert into perovskite immediately after preparation. This provides a feasible solution for the subsequent large-scale industrial preparation of perovskite.
[0072] As an optional implementation, the pore-forming agent can be a mixture of the above-mentioned volatile organic salts, inorganic salts and dehydrating pore-forming agents, or only dehydrating pore-forming agents can be used. Preferably, the dehydrating pore-forming agent is selected from monomeric or polymeric carbodiimides, isocyanates, oxazoline compounds, epoxy compounds and other volatile and dehydrating pore-forming agents.
[0073] Preferably, the pore-forming agent has a functional group of -N=C=N-. Such compounds with the above functional group are often used as anti-hydrolysis agents or dehydrating agents in chemical reactions, also known as carbodiimide structures, which refer to a class of compounds containing the functional group -N=C=N- in the molecule. The pore-forming agent only needs to contain the above functional group to have the functions of pore-forming and dehydrating.
[0074] Carbodiimide can be divided into monomeric carbodiimide anti-hydrolysis agent and polymeric carbodiimide anti-hydrolysis agent. Among them, the monomeric carbodiimide anti-hydrolysis agent contains only one functional group in the molecule, and is a bright yellow to brown liquid or crystalline solid at room temperature. The advantage of the monomeric carbodiimide hydrolyzing agent is that it has high activity. The polymeric carbodiimide anti-hydrolysis agent contains more than two functional groups in the molecule, and is a yellow to brown flaky powder at room temperature, and has the advantage of low toxicity. The present invention does not make special restrictions on carbodiimide compounds, which can be at least one of monomeric and polymeric types. The present invention does not make special restrictions on the functional group grafted with carbodiimide. Preferably, the pore-forming agent includes at least one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide.
[0075] In step S120, the present invention does not specifically limit the method for forming the porous lead halide skeleton layer, as long as the lead halide and the pore-forming agent can be formed together, for example, by chemical solution; or by magnetron sputtering.
[0076] As an optional implementation, a method of co-evaporation of multiple evaporation sources is adopted, and the evaporation sources are set to lead halide and pore-forming agent, and co-evaporation is performed to form a lead halide layer. This co-evaporation method allows the lead halide and the pore-forming agent to be deposited together and simultaneously, so that the lead halide layer formed by evaporation contains this pore-forming agent from the bottom to the surface. The position of the pore-forming agent in the film layer is the position where the pores are generated in the subsequent volatilization. Therefore, this co-evaporation preparation method can control the evaporation time, evaporation rate and other evaporation parameters of the pore-forming agent to control and adjust the position of the pore-forming agent in the lead halide layer, so that the pore path or pore channel can be designed to prepare the corresponding pore distribution structure.
[0077] The present invention does not impose any special restrictions on the method of forming pores with the pore-forming agent, and only requires that the pore-forming agent be volatilized. For example, the pore-forming agent may be volatilized by annealing and heating to form pores; for another example, the pore-forming agent may be naturally volatilized to form pores by increasing the gas flow rate.
[0078] In some embodiments, the coating material forms a porous lead halide skeleton layer with a preset porosity on the first surface of the initial film layer through an evaporation process, specifically comprising:
[0079] The container containing the lead halide and the container containing the pore-forming agent are heated respectively, so that the lead halide and the pore-forming agent evaporate and are co-deposited on the first surface of the initial film layer to form a lead halide layer;
[0080] The lead halide layer is subjected to a second type annealing treatment so that the pore former is evaporated by heat to form a porous lead halide skeleton layer; wherein the ratio of the deposition rate of the lead halide to the deposition rate of the pore former is between 10:1 and 20:1; and the preset porosity is between 1% and 30%.
[0081] The present invention does not impose any special restrictions on the evaporation parameters, and it is only necessary to satisfy the requirement that the lead halide and the pore-forming agent are co-evaporated as two evaporation sources. Specifically, the lead halide and the pore-forming agent are placed in a heating crucible for evaporation as evaporation sources, which are heated separately or together, and the evaporation sources evaporate and cool and deposit on the initial film layer.
[0082] It is understandable that in order to allow the pore former to exist inside the lead halide layer from the surface layer to the bottom layer, it is critical to evaporate and deposit at the same time to achieve the effect of co-deposition. If the pore former only exists at the bottom of the lead halide, there may be a risk of not being able to completely volatilize and form holes. On the contrary, if the pore former only exists on the surface of the lead halide, that is, the top, there will be no pore former at the bottom, so that no holes can be formed at the bottom to allow the subsequent organic amine salt solution to penetrate.
[0083] In order to control the proportion of the pore former in the deposited lead halide layer, the pore former and the lead halide are placed in different heating crucibles for evaporation. This setting can control the evaporation rate of different evaporation sources by controlling the heating temperature of different crucibles respectively, and then control the deposition rate of the corresponding evaporation source to form lead halide layers with different pore former contents.
[0084] The present invention does not impose any special restrictions on the heating temperature, evaporation rate, and deposition rate. For example, in order to obtain more holes and make it less likely to absorb moisture, or to place the first film layer for a longer time and make it less likely to degrade or hydrolyze, the deposition rate of the pore former can be increased by increasing the heating temperature of the pore former crucible, so that in the same time, the deposition rate of the pore former is faster and its proportion is larger, but the content of the pore former should not be too much. Excessive content of the pore former may result in poor quality of the lead halide layer, or even too loose to form a film, with many defects, which is not conducive to the formation of high-quality perovskite film; preferably, the deposition rate of the lead halide is greater than the deposition rate of the pore former, so that the proportion of the pore former is smaller and the defects formed are fewer, but at the same time, a subsequent porous lead halide skeleton layer can also be produced. Preferably, the ratio of the deposition rate of the lead halide gas to the deposition rate of the pore former is between 10:1 and 20:1; the preset porosity is between 1% and 50%.
[0085] In some embodiments, the heating temperature of the lead halide is in the range of 350°C to 480°C, the heating temperature of the pore former is in the range of 80°C to 130°C, and accordingly, the deposition rate of the lead halide gas is in the range of to The deposition rate of the pore former is between to between.
[0086] For example, the crucible containing the pore former can be heated to a higher temperature at the initial stage to increase the deposition rate of the pore former, so that the content of the pore former is greater than that of the lead halide at the beginning of evaporation, thereby forming more pore formers at the bottom, and then the heating rate is reduced to facilitate the formation of a lead halide layer with better quality.
[0087] In addition, due to the dehydration of the pore-forming agent, the lead halide layer is resistant to moisture and heat, and has good wet heat stability. Therefore, after the lead halide layer is formed, there is no need to worry about the problem of water vapor adsorption and immediately carry out the coating of the next step of organic amine salt. The lead halide layer can be stored for a certain period of time without hydrolysis, pyrolysis and other problems, and will not affect the film quality of the subsequent perovskite film, and improve the time length and stability of the lead halide layer. Therefore, the pore-forming agent introduced by the present invention can make it possible to prepare perovskite on a large scale industrially, greatly reducing the cost and process difficulty. In some embodiments, the lead halide layer added with the pore-forming agent is placed in the air or in a humid environment for several hours, and it will not fail. The perovskite film formed subsequently has high film quality, and the electrical properties will not be affected and significantly decreased, and due to the formation of a porous structure, the reaction activity is improved, so that the crystallinity of the perovskite film is increased, and the electrical conductivity is improved instead.
[0088] The lead halide layer is subjected to a second type of annealing treatment, so that the pore-forming agent is accelerated to volatilize and overflow from the lead halide layer, which can destroy the dense lead halide prepared by evaporation and form a porous lead halide skeleton layer. In addition, the water vapor of the lead halide layer can also be heated and evaporated. In order to make the pore-forming agent volatilize as soon as possible and completely volatilize without residue, it is preferred that the annealing temperature is not lower than the boiling point of the pore-forming agent. In some embodiments, the annealing temperature is between 150°C and 170°C, and the annealing time is between 3min and 7min. The annealing temperature should not be too high. An excessively high annealing temperature makes the lead halide layer more dense, which is not conducive to the further penetration and reaction of the organic amine salt. However, the annealing temperature should not be too low. Too low a temperature cannot completely volatilize the pore-forming agent into a gas, and there will be residual pollution of the pore-forming agent, which will cause defects in the subsequent perovskite film.
[0089] Annealing volatilizes the pore-forming agent to form a porous lead halide skeleton layer, which is more favorable for the second step of wet organic amine salt solution coating. The organic amine salt solution can penetrate into the porous lead halide skeleton in the form of liquid. The porous channels in the porous lead halide skeleton ensure that the organic amine salt solution can continue to diffuse from the surface of the lead halide to the bottom of the lead halide, allowing the lead halide to fully contact with the organic amine salt solution and react chemically to form a perovskite film, thereby enhancing the conversion and crystallization of the perovskite film and improving the performance of solar cells. In conventional solar cells, due to the lack of a porous structure, the lead halide will form a dense film. If the conventional film growth method of soaking in an organic amine salt solution is used, only the lead halide on the surface can contact and react with the organic amine salt, and only a thin layer of perovskite is generated on the surface, which causes a large amount of lead halide residue in the film, resulting in insufficient light absorption of the active layer and a large charge transfer resistance, thereby reducing the performance of the solar cell. In addition, the pore-forming agent is volatile and evaporates and disappears during the subsequent heating process, avoiding the introduction of impurities that affect the synthesis quality of the perovskite film.
[0090] In step S130, the present invention does not specifically limit the coating method. For example, the organic amine salt solution can be brought into contact with the porous lead halide skeleton layer and reacted by immersion, smearing, scraping, slit coating, etc.
[0091] In some embodiments, coating a mixed solution of organic amine salts on a side of the porous lead halide skeleton layer away from the initial film layer to react and form an initial perovskite film specifically comprises: spin coating the organic amine salt solution on the porous lead halide skeleton layer to obtain an initial perovskite film;
[0092] Among them, relying on the centrifugal force and gravity generated when the substrate rotates, the organic amine salt solution drops falling on the surface of the porous lead halide skeleton layer are fully distributed, and a flat coating of uniform thickness can be obtained. Compared with other coating methods, the spin coating method is simple and easy to operate, and a flat coating can be achieved on a substrate with a large thickness range, saving costs. At the same time, the organic amine salt flows on the surface of the porous lead halide skeleton layer in a liquid manner, and it is easy to fill into the porous structure, so that the organic amine salt penetrates into the interior of the film layer, and reacts fully with the lead halide to generate more perovskite. The solute in the organic amine salt solution is selected from at least one of formamidine hydroiodide, formamidine hydrobromide, methyl iodide ammonium, methyl bromide ammonium and methyl ammonium chloride, and the solvent in the organic amine salt solution is selected from at least one of isopropanol, ethanol and methanol. Using the above components as the solvent of the organic salt, on the one hand, most of the organic amine salt can be well dissolved; on the other hand, the solvent will not destroy the lead halide skeleton structure, and the above solvent can evaporate during the spin coating process, leaving only the organic amine salt solute to react with the lead halide to generate perovskite.
[0093] Preferably, the distance between the coating blade and the first substrate is between 100 and 500 μm, the coating speed is between 10 mm / s and 20 mm / s, and the injection speed is between 10 μL / s and 20 μL / s. The above parameters can form a perovskite film that meets the thickness requirements, but the present invention does not specifically limit the coating parameters. The coating parameters can be adjusted according to different thickness requirements, film-forming properties, etc., and the flow and spreading of the liquid can be controlled to obtain perovskite films with different structures and properties. For example, in order to increase the thickness of the perovskite film, the lead halide layer deposition thickness is increased, while the coating time is extended and the coating speed is reduced, the liquid is subjected to a smaller centrifugal force, so that the coating thickness increases.
[0094] In step S140, the initial perovskite film is subjected to a first type annealing treatment to form a perovskite film, specifically comprising: performing a first type annealing treatment on the initial perovskite film to form a perovskite film, wherein the annealing temperature is between 120° C. and 160° C., and the annealing time is between 5 minutes and 30 minutes.
[0095] The initial perovskite film is annealed to form a perovskite film. If the annealing temperature is too high, the perovskite crystal structure will be destroyed and the perovskite will be decomposed. However, if the annealing temperature is too low, it will not be enough to completely volatilize the organic solvent, resulting in incomplete crystallization of the perovskite. Preferably, the annealing temperature is between 120°C and 160°C, and the annealing time is between 5 minutes and 30 minutes.
[0096] The perovskite film obtained based on the above-mentioned perovskite film preparation method can be further prepared to obtain a single-junction perovskite battery, or a crystalline silicon-perovskite stacked battery can be obtained.
[0097] For example, when preparing a single-junction perovskite cell, a feasible step includes: sequentially forming an electron transport layer, a second transparent conductive layer, and a metal electrode on the perovskite film. For another example, when preparing a crystalline silicon-perovskite stacked cell, a feasible step includes: preparing a crystalline silicon bottom cell and a perovskite cell stacked in sequence. The following is a detailed description of the relevant method.
[0098] See also Figure 2 , is a schematic flow chart of a specific implementation method of the method for preparing a perovskite battery of the present invention, the steps comprising:
[0099] In step S200, a first transparent conductive layer 11a is provided; preferably, the first transparent conductive layer 11a is selected from indium tin oxide, and indium tin oxide is plated on the target film layer by magnetron sputtering to obtain the first transparent conductive layer. In some embodiments, conductive glass of indium tin oxide or an indium tin oxide layer can also be directly selected as the first transparent conductive layer.
[0100] For example, in order to improve the bonding strength between the subsequent film layer and the first transparent conductive layer 11a and reduce defects, the transparent conductive oxide glass (ITO) substrate is preferably cleaned with ethanol and then dried with nitrogen for later use.
[0101] In step S210, a first carrier transport layer 12 is formed on one side of the first transparent conductive layer 11a; wherein the first carrier transport layer 12 is, for example, a hole transport layer; illustratively, the hole transport layer can be an inorganic metal oxide, such as any one of nickel oxide, aluminum oxide, molybdenum oxide or vanadium oxide, or an organic polymer, such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].
[0102] For example, a radio frequency power source with a sputtering power of 400 W is used to physically sputter and deposit nickel oxide with a thickness of 20 nm on the first transparent conductive layer 11 a as a hole transport layer.
[0103] In step S220, the first carrier transport layer is used as the initial film layer, and the perovskite film 13 is prepared on the side of the first carrier transport layer 12 away from the first transparent conductive layer by the preparation method of the perovskite film of the present invention; this step specifically includes:
[0104] A lead halide layer with a thickness of 300 nm is formed by co-evaporation deposition using multiple evaporation sources on the surface of the first carrier transport layer 12 away from the first transparent conductive layer 11a, wherein the evaporation sources are lead iodide, lead bromide and polycarbodiamine. Preferably, the deposition rate of lead iodide is The deposition rate of lead bromide is The deposition rate of polycarbodiamine is The lead halide layer was deposited to a thickness of 300 nm.
[0105] The sample is moved to a constant temperature hot stage, and the lead halide layer is subjected to a second type annealing treatment to form a porous lead halide skeleton layer, wherein the annealing temperature is 160° C. and the annealing time is 5 min;
[0106] Formamidine hydroiodide, methyl ammonium bromide and methyl ammonium chloride are mixed and dissolved in isopropanol or ethanol in a mass ratio of 60:6:6 to prepare an organic amine salt solution. 100 μL of the organic amine salt solution is spin-coated at a rate of 2000 rpm on the surface of the porous lead halide skeleton layer away from the first transparent conductive layer 11a. Spin coating for 30 seconds to obtain an initial perovskite film.
[0107] The sample was moved to a constant temperature hot stage, and the initial perovskite film was subjected to a first type annealing treatment to form a perovskite film 13, wherein the annealing temperature was 150°C and the annealing time was 10 minutes.
[0108] In step S230, a second carrier transport layer 14, a second transparent conductive layer 11b and a first metal electrode 15a are sequentially stacked on the side of the perovskite film 13 away from the first carrier transport layer 12, specifically including:
[0109] A second carrier transport layer 14 (eg, an electron transport layer) is deposited on the side of the perovskite film 13 away from the first carrier transport layer 12. Preferably, the electron transport layer comprises a stack of carbon 60 (C 60 ) and tin oxide (SnO2) double electron transport layer; among them, C 60 Prepared by thermal evaporation, the evaporation rate is The thickness is 20nm. SnO2 is prepared by atomic layer deposition with a thickness of 20nm;
[0110] A transparent conductive oxide layer is deposited on the side of the electron transport layer away from the perovskite film 13 as the second transparent conductive layer 11b. Preferably, the transparent conductive oxide layer is an indium zinc oxide film (IZO) prepared by magnetron sputtering with a thickness of 60nm.
[0111] A first metal electrode 15a is deposited on the side of the second transparent conductive layer 11b away from the second carrier transport layer 14 to obtain a perovskite cell. Preferably, a 100nm thick silver metal layer is prepared by evaporation as the first metal electrode 15a.
[0112] The perovskite film in the perovskite cell prepared by the above method has high crystallinity, high conversion rate, few defects, no other impurity phases remain, and its conductivity is also higher. The present invention does not specifically limit the structure of the single-junction perovskite cell, and it only needs to meet the requirements of using the above preparation method to prepare the perovskite film. For example, a buffer layer can be added after the electron transport layer is prepared to reduce the sputtering damage of the second transparent conductive layer. For another example, the hole transport layer and the electron transport layer are interchanged to change the direction of the current.
[0113] See also Figure 4 and Figure 5 As another aspect of the present invention, a method for preparing a laminated battery and a laminated battery are provided, comprising:
[0114] Step S300, providing a crystalline silicon bottom cell 2; the crystalline silicon bottom cell 2 includes a front side and a back side opposite to each other;
[0115] Step S310 , preparing a perovskite cell 1 on the front side of the crystalline silicon bottom cell 2 .
[0116] The crystalline silicon bottom cell 2 includes the following stacked in sequence: a second metal electrode 15b, a third transparent conductive layer 11c, a second type doped silicon layer 24, an intrinsic layer 22, a silicon substrate 23, an intrinsic layer 22 and a first type doped silicon layer 21. The present invention does not specifically limit the structure of the crystalline silicon-perovskite stacked cell. The silicon substrate can be an N-type or P-type silicon substrate. Accordingly, the first type doped silicon layer and the second type doped silicon layer are adaptively adjusted, and the hole transport layer and the electron transport layer of the perovskite cell are also interchanged accordingly.
[0117] By way of example, the crystalline silicon bottom cell 2 includes: a PERC cell, a BC cell, a HJT cell or a TOPCon cell.
[0118] The present invention will be further explained below in conjunction with the embodiments.
[0119] Preparation Example
[0120] Prepare the initial membrane layer as follows:
[0121] The transparent conductive oxide glass substrate (ITO) was cleaned with ethanol and dried with nitrogen;
[0122] Using a radio frequency power supply with a sputtering power of 400W to physically sputter and deposit nickel oxide with a thickness of 20nm as a hole transport layer on the transparent conductive oxide glass substrate to obtain an initial film layer;
[0123] Example
[0124] Example 1
[0125] A method for preparing a perovskite film, comprising:
[0126] Step 1: Form a porous lead halide skeleton layer on the surface of the hole transport layer on the side of the initial film layer obtained in the preparation example by evaporation, wherein the evaporation source includes lead halide and a pore-forming agent, and the pore-forming agent has dehydration. Specifically, lead iodide, lead bromide and polycarbodiamine are respectively placed in multiple evaporation heating crucibles as evaporation sources, and each evaporation source fills about 2 / 3 of the crucible. The three evaporation sources are heated together for evaporation to obtain a lead halide layer with a thickness of 300 nm, wherein the evaporation temperature of lead iodide is 420° C., the evaporation temperature of lead bromide is 465° C., and the evaporation temperature of polycarbodiamine is 118° C. Using a quartz crystal microbalance (QCM) as a rate measuring probe, the deposition rate of lead iodide is The deposition rate of lead bromide is The deposition rate of polycarbodiamine is The initial film layer deposited with the lead halide layer is moved to a constant temperature hot plate for annealing to form a porous lead halide skeleton layer. The heating temperature is 160° C. and the heating time is 5 min.
[0127] Step 2, coating an organic amine salt mixed solution on the surface of the porous lead halide skeleton layer away from the initial film layer, and annealing. Specifically, first, formamidine hydroiodide, methyl ammonium bromide, and methyl ammonium chloride are mixed in a mass ratio of 60:6:6 and dissolved in isopropanol or ethanol to prepare an organic amine salt solution, and 100 μL of the organic amine salt solution is dripped on the surface of the porous lead halide skeleton layer away from the initial film layer. Spin coating at a rate of 2000 rpm for 30 seconds, and the distance between the coating head and the substrate is 300 μm; the coating speed is 15 mm / s, and the injection speed is 15 μL / s to obtain an initial perovskite film. The initial perovskite film coated with the solution is moved to a constant temperature hot stage for annealing. The annealing temperature is 150°C, and the annealing is 10 minutes to form a perovskite film as sample 1.
[0128] Comparative Example 1
[0129] The perovskite film was prepared by the same preparation method as in Example 1, except that, when evaporating the lead halide layer in step 1, only two evaporation sources, lead iodide and lead bromide, were used to prepare the formed perovskite film, which was sample 2.
[0130] Test Example 1
[0131] The microstructure of the lead halide layer formed by the preparation method of the above-mentioned embodiment 1 and the comparative example is observed by scanning electron microscope, as shown in Figure 6 (a) and Figure 6 (b); the lead halide layer formed by the preparation method of the above-mentioned embodiment 1 and the comparative example is photographed by camera, as shown in Figure 7 (a) and Figure 7 (b). It can be seen from Figure 6 (a) and Figure 6 (b) that by introducing polycarbodiamine in the process of evaporating the lead halide layer, a porous lead halide skeleton can be prepared. The lead halide layer of Figure 6 (a) has holes on its surface, while the surface of the comparative example of Figure 6 (b) is a dense lead halide layer without holes.
[0132] After coating the lead halide layer with an organic amine salt, the lead halide layer can be fully converted into perovskite. The perovskite film prepared in Example 1, as shown in FIG7(a), is darker and more uniformly distributed, indicating that the thickness of the formed perovskite film is more uniform, and the crystallinity of the perovskite is higher, indicating that the reaction is more complete and the quality is better. The perovskite film prepared in the comparative example, as shown in FIG7(b), has an uneven macroscopic color distribution, the yellow area is the color of the unreacted lead halide, and there is only a small amount of perovskite in the black area, indicating that the conversion reaction is not sufficient, the perovskite conversion rate is low, and the crystallinity is low.
[0133] The surface of the perovskite film formed by the preparation method of Example 1 and Comparative Example 1 of the present invention was tested by an X-ray diffractometer to obtain the X-ray diffraction test graphs in Example 1 and Comparative Example 1, as shown in FIG. Figure 8 As shown, the results show that the XRD test results of Example 1 show that when the diffraction angle is 12.7°, there is no characteristic peak of lead halide, which proves that the porous lead halide skeleton layer prepared by polycarbodiamine can completely react with the organic amine salt solution to generate perovskite, the reaction is sufficient, and the perovskite is completely formed without lead halide residue. The XRD test results of Comparative Example 1 show that there is a characteristic peak of lead halide when the diffraction angle is 12.7°, which shows that the lead halide layer of the comparative example does not react sufficiently with the organic amine salt solution, and there is still lead halide residue in the formed perovskite.
[0134] Example 2
[0135] Example 2 provides a method for preparing a perovskite cell, wherein the perovskite film is prepared by the same preparation method as in Example 1, except that the method further comprises the following steps:
[0136] An electron transport layer, a transparent conductive oxide layer and a metal electrode are sequentially formed on the perovskite film to obtain the perovskite cell. Specifically, an electron transport layer is prepared on the surface of the perovskite film, and the electron transport layer is a double electron transport layer structure of carbon 60 (C60) and tin oxide (SnO2), wherein C60 is prepared by thermal evaporation at a rate of The thickness is 20nm, SnO2 is prepared by atomic layer deposition, and the thickness is about 20nm; a transparent conductive layer is prepared on the above electron transport layer, and the transparent conductive layer is indium zinc oxide (IZO), which is prepared by magnetron sputtering and has a thickness of 60nm; a metal electrode is prepared on the above transparent conductive layer, and the thickness is about 20nm. -4 Pa under high vacuum 100 nm of Ag was evaporated at an evaporation rate of , and finally a single-junction perovskite cell 1 was prepared.
[0137] Example 3
[0138] The perovskite cell was prepared by the same preparation method as in Example 2, except that after the lead halide layer was prepared, the initial perovskite film was left to stand at an air humidity of about 40% for 24 hours, and finally a single-junction perovskite cell 2 was prepared.
[0139] Comparative Example 2
[0140] The perovskite cell was prepared by the same preparation method as in Example 2, except that, when evaporating the lead halide layer, only two evaporation sources, lead iodide and lead bromide, were used to prepare the lead halide layer, and finally a single-junction perovskite cell 3 was prepared.
[0141] Comparative Example 3
[0142] The perovskite cell is prepared by the same preparation method as in Example 2, except that, when evaporating the lead halide layer, only two evaporation sources, lead iodide and lead bromide, are used to prepare the lead halide layer, and after the lead halide layer is prepared, the initial perovskite film is left to stand at an air humidity of approximately 40% for 24 hours, and finally a single-junction perovskite cell 4 is prepared.
[0143] Test Example 2
[0144] In this test example, Suzhou Weixin VS-6831S equipment was used to test the photoelectric performance of the perovskite cells prepared in Example 2, Example 3 and Comparative Example 2, Comparative Example 3, and the current-voltage (JV) curve was obtained. Fig. 9 Shown is a comparison of the current-voltage (JV) curves of Example 2 and Comparative Example 2, Fig.10 Shown is a comparison of the current-voltage (JV) curves of Example 3 and Comparative Example 3.
[0145] Table 1 records the photoelectric performance parameters of the embodiments and comparative examples extracted from the JV curves, wherein Voc represents the open circuit voltage, Jsc represents the short circuit current density, FF represents the fill factor, and PCE represents the photoelectric conversion efficiency.
[0146] The JV test curve and the electrical parameter results in Table 1 show that when the perovskite battery is not connected to any load, the current is at its minimum value, and the voltage across the battery is at its maximum value, which is called the perovskite battery open circuit voltage (Voc), reflecting the maximum voltage output capacity of the perovskite battery under standard test conditions. The open circuit voltage is mainly affected by the composite effect. The porosity and dehydration of the lead halide layer in Examples 2 and 3 enhance the permeation conversion of the organic amine salt. The reaction is sufficient when preparing the perovskite and no hydrolysis decay occurs. The final perovskite light absorption layer has a high conversion rate and high crystallinity. The open circuit voltage of the perovskite battery is improved, its filling factor is improved, and the conversion efficiency is also significantly improved. In contrast, Comparative Examples 2 and Comparative Examples 3 are dense because the generated lead halide layer cannot fully react with the organic amine salt, and the prepared perovskite has a low conversion rate and low crystallinity. The final perovskite battery has a low open circuit voltage, and the corresponding filling factor and conversion efficiency are also significantly reduced.
[0147] After the lead halide layer was prepared, both Example 3 and Comparative Example 3 were left to stand at 40% air humidity for 24 hours. The JV test curve and the electrical parameter results in Table 1 showed that in Example 3, polycarbodiamine was added during the evaporation of the lead halide layer to plunder the moisture in the lead halide layer, thereby improving the moisture resistance of the lead halide layer in a humid environment and increasing its long-term aging time. The corresponding perovskite battery did not experience a decrease in electrical parameters. It can be obtained that the perovskite film did not absorb moisture and hydrolyze due to the long-term placement of the lead halide layer, resulting in performance degradation. On the contrary, in Comparative Example 3, because no pore-forming agent was added, the long-standing lead halide layer absorbed more moisture. In the subsequent reaction to form perovskite, the perovskite was hydrolyzed when it met water, the crystallinity decreased, the conversion rate decreased, and finally the performance of the perovskite battery declined significantly.
[0148] Table 1
[0149] <![CDATA[V oc (V)]]> <![CDATA[J sc (mA / cm 2 )]]> FF(%) PCE(%) Example 2 1.165 20.68 0.81 19.69 Example 3 1.161 20.05 0.81 20.74 Comparative Example 2 1.078 21.08 0.78 17.72 Comparative Example 3 1.131 20.02 0.60 14.94
[0150] As can be seen from Table 1, by introducing a pore former during the process of evaporating the lead halide layer, the pore former has dehydration and volatility, creating a lead halide layer with a porous skeleton structure, enhancing the permeation conversion of organic amine salts, and significantly improving the photoelectric conversion efficiency of the perovskite battery. At the same time, the pore former can plunder the moisture in the lead halide layer, improve the moisture resistance of the lead halide layer in a humid environment, increase its long-term aging time, and significantly reduce the attenuation of the perovskite battery performance caused by the moisture absorption of the lead halide layer in a humid environment for a long time.
[0151] Example 4
[0152] A method for preparing a crystalline silicon-perovskite tandem cell is provided, which specifically comprises:
[0153] Providing an initial silicon substrate, wherein the initial silicon substrate is a 4-inch n-type silicon wafer with a thickness of 260 μm to 280 μm;
[0154] The initial silicon substrate is subjected to double-sided texturing treatment. Specifically, the initial silicon substrate is placed in an alkaline solution to prepare a double-sided texturing structure with randomly distributed pyramids. The size of the pyramids is controlled by adjusting the concentration of the alkaline solution and the process temperature. The silicon substrate after texturing is subjected to acid immersion treatment in a hydrofluoric acid solution and then cleaned to remove the residual solution and form a clean surface.
[0155] The silicon substrate after the above treatment is deposited with an amorphous silicon thin film by plasma enhanced vapor chemical deposition. Specifically, an 8 nm intrinsic amorphous silicon layer is first deposited on the front and back surfaces of the silicon substrate, and then a 6 nm phosphorus-doped amorphous silicon layer is deposited on the intrinsic amorphous silicon layer on the front surface, and a 13 nm boron-doped amorphous silicon layer is deposited on the intrinsic amorphous silicon layer on the back surface, and the deposition temperature is 200° C.
[0156] A 100 nm ITO film is deposited on the surface of the boron-doped amorphous silicon layer by magnetron sputtering, and a 20 nm ITO film is deposited on the surface of the phosphorus-doped amorphous silicon layer by magnetron sputtering;
[0157] A 1 μm Ag electrode is deposited on the ITO film on the back of the silicon substrate by magnetron sputtering, and then annealed to recover the sputtering damage, wherein the annealing temperature is 200° C. and the annealing time is 10 minutes, to obtain a crystalline silicon cell;
[0158] A hole transport layer is prepared on the front side of the crystalline silicon solar cell by using the same preparation method as in the preparation example;
[0159] A single-junction perovskite cell was prepared on the hole transport layer using the same preparation method as in Example 2, except that the pore-forming agent was isocyanate and the thickness of the front Ag electrode was 1 μm, and finally a crystalline silicon-perovskite stacked cell 5 was prepared.
[0160] Comparative Example 4
[0161] The crystalline silicon-perovskite stacked cell is prepared by the same preparation method as in Example 4, except that, when evaporating the lead halide layer, only two evaporation sources, lead iodide and lead bromide, are used to prepare the lead halide layer, and finally the crystalline silicon-perovskite stacked cell 6 is prepared.
[0162] Test Example 3
[0163] The photoelectric performance of the crystalline silicon-perovskite tandem cells prepared in Example 4 and Comparative Example 4 was tested using Suzhou Weixin VS-6831S equipment to obtain a current-voltage (JV) curve, as shown in FIG. Fig.11 , which is a comparison of the current-voltage (JV) curves of Example 4 and Comparative Example 4. Table 2 records the photoelectric performance parameters of Example 4 and Comparative Example 4 extracted from the JV curves.
[0164] Table 2
[0165] <![CDATA[V oc (V)]]> <![CDATA[J sc (mA / cm 2 )]]> FF(%) PCE(%) Example 4 1.83 20.19 0.787 29.14 Comparative Example 4 1.72 19.47 0.751 25.16
[0166] pass Fig.11 The JV test curve and the electrical parameter results in Table 2 show that the pore-forming agent introduced in the process of evaporating the lead halide layer in the present invention has dehydration and volatility, and creates a lead halide layer with a porous skeleton structure, so that the prepared lead halide layer has porosity and dehydration, enhances the permeation conversion of the organic amine salt, and the reaction is sufficient when preparing the perovskite and no hydrolysis decay occurs. The final perovskite light-absorbing layer has a high conversion rate and high crystallinity. When it is applied to the perovskite-crystalline silicon stacked battery, the open circuit voltage of the battery is increased, the maximum current density is increased, the filling factor is increased, and the conversion efficiency is also significantly improved. In contrast, in Comparative Example 4, due to the dense lead halide layer generated, the organic amine salt cannot be fully reacted, the prepared perovskite conversion rate is low, the crystallinity is low, and the final crystalline silicon-perovskite stacked battery has a low open circuit voltage, and the corresponding filling factor and conversion efficiency are also significantly reduced.
[0167] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Those skilled in the art should understand that the present application includes but is not limited to the contents described in the drawings and the above specific implementations. Any modification that does not deviate from the functional and structural principles of the present application will be included in the scope of the claims.
Claims
1. A method for preparing a perovskite film, characterized in that: The preparation method comprises: Providing an initial film layer, the initial film layer comprising a first surface and a second surface opposite to each other; Providing a coating material, the coating material comprising: lead halide and a pore-forming agent; wherein the pore-forming agent has a dehydrating property; The coating material forms a porous lead halide skeleton layer with a preset porosity on the first surface of the initial film layer through an evaporation process; Coating a mixed solution of organic amine salts on a side of the porous lead halide skeleton layer away from the initial film layer to react and form an initial perovskite film; The initial perovskite film is subjected to a first type annealing treatment to form the perovskite film.
2. The preparation method according to claim 1, characterized in that: The molecular formula of the pore former has a -N=C=N- functional group.
3. The preparation method according to claim 2, characterized in that: The pore-forming agent includes at least one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide.
4. The preparation method according to claim 1, characterized in that: The step of forming a porous lead halide skeleton layer with a preset porosity on the first surface of the initial film layer by a evaporation process of the coating material comprises: Heating the container containing the lead halide and the container containing the pore-forming agent respectively, so that the lead halide and the pore-forming agent evaporate and are co-deposited on the first surface of the initial film layer to form a lead halide layer; The lead halide layer is subjected to a second type annealing treatment so that the pore former is evaporated by heat to form the porous lead halide skeleton layer; wherein, The ratio of the deposition rate of the lead halide to the deposition rate of the pore former is between 10:1 and 20:1; The preset porosity is between 1% and 30%.
5. The preparation method according to claim 4, characterized in that: The lead halide is heated at a temperature in the range of 350° C. to 480° C.; The lead halide deposition rate is to between; The heating temperature of the pore former is in the range of 80°C to 130°C; The deposition rate of the pore former is to between.
6. The preparation method according to claim 4, characterized in that: In the step of performing a second type annealing treatment on the lead halide layer, the annealing temperature is not lower than the boiling point of the pore former, wherein: The annealing temperature is in the range of 150°C to 170°C; The annealing time is between 3min and 7min.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step of coating a mixed solution of organic amine salts on a side of the porous lead halide skeleton layer away from the initial film layer to react and form an initial perovskite film, and performing a first type annealing treatment on the initial perovskite film to form the perovskite film, The solute in the organic ammonium salt solution is selected from at least one of formamidine hydroiodide, formamidine hydrobromide, methylammonium iodide, methylammonium bromide and methylammonium chloride; The solvent in the organic ammonium salt solution is selected from at least one of isopropanol, ethanol and methanol; In the first type annealing treatment, the annealing temperature is in the range of 120° C. to 160° C.; and the annealing time is in the range of 5 min to 30 min.
8. A method for preparing a perovskite battery, characterized in that: include: providing a first transparent conductive layer; forming a first carrier transport layer on one side of the first transparent conductive layer; Using the first carrier transport layer as an initial film layer, and using the preparation method described in any one of claims 1 to 7 to prepare a perovskite film on a side of the first carrier transport layer away from the first transparent conductive layer; A second carrier transport layer, a second transparent conductive layer and a first metal electrode stacked in sequence are formed on a side of the perovskite film away from the first carrier transport layer.
9. A method for preparing a laminated battery, characterized in that: include: A crystalline silicon bottom cell is provided; the crystalline silicon bottom cell comprises a front side and a back side opposite to each other; A perovskite cell is prepared on the front side of the crystalline silicon bottom cell; wherein, The perovskite battery is prepared by the preparation method according to claim 8; The crystalline silicon bottom cell includes: a PERC cell, a BC cell, a HJT cell or a TOPCon cell.
10. A laminated battery, characterized in that: The method according to claim 9 is used to prepare the laminated battery, wherein the laminated battery comprises: a crystalline silicon bottom battery and a perovskite battery stacked in sequence; wherein: The crystalline silicon bottom cell includes: a PERC cell, a BC cell, a HJT cell or a TOPCon cell.
Citation Information
Cited By
Perovskite thin film, preparation method therefor, cell, and preparation method therefor
WO2026119010A1